A comparative study of magnesium sulphate and isoxsuprine as a tocolytic in preterm labour - Mathuriya, Gayatri; Tarware, Ritu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Preterm birth is a significant health problem across the world because of associated neonatal mortality and short-and long-term morbidity in later life. The incidence in India is higher than developed countries. Methods: The present study conducted in the Department of Obstetrics and Gynaecology, MGM Medical College and M. Y. Hospital. Indore, (Madhya Pradesh). The patients selected from labour rooms.100 antenatal women of gestational age between 28 weeks to 37 weeks presenting with preterm labor, 50 in each group. Group A consisted women receiving magnesium sulphate, group B had women receiving isoxsuprine. Efficacy of the two tocolytics, prolongation of pregnancy and neonatal outcome in preterm labour was assessed. Results: Intravenous magnesium sulphate was much effective in postponement of preterm labour for at least 48 hours (74%) as compared to isoxsuprine (50%). As a cervical dilatation, effacement increased the success rate of both the drugs came down. Magnesium sulphate side effects were better monitored clinically and tolerated. Also, better neonatal outcome and lesser perinatal mortality were noticed in this group (24%) compared to isoxsuprine (54%). Conclusions: Prematurity is the one of the major risk factor determing perinatal outcome. There is no ideal tocolytic, short term prolongation till steroid coverage for lung maturit with minimum side effects and to achieve better perinatal outcome recommended. The number of nursery admissions of preterm babies with better perinatal outcome were observed with magnesium sulphate. Also, the number of nursery admissions of preterm babies were less when treated with magnesium sulphate as tocolytic (also found to have neuroprotective effects in various studies), as compared to isoxsuprine.